Pushing our understanding of diversity in organizations - King, Eden; Roberson, Quinetta M.; Hebl, Michelle R. (Research on social issues in management, 2020)
"Few time periods in the past five decades match the intensity of intergroup conflict that people around the world are currently experiencing. Polarized attitudes around various sociopolitical issues, such as gender equality and immigration, have dominated the media and our lives. Furthermore, these powerful social dynamics have also impacted the places where we work and intensified existing strains on workers and workplaces. To address these issues and improve organizational climates, more theories, research and collaborations to understand these phenomena are needed. The volumes in this series will describe and instigate scholarship that advances our understanding of diversity in organizations. This volume features renowned scholars who are unabashedly pushing the field by raising the questions that need to be asked, by working on topics that have received far too little research attention, and by holding researchers, practitioners, managers, organizations, and readers to task for doing what needs to be done to maximize social justice and egalitarian behaviors in the workplace. The chapters provoke the status quo in society and in scholarship, and in so doing, push our understanding of diversity in organizations"--